Reluctant roommates - Quinn, Tara Taylor (Harlequin special edition, 2022)
"He just inherited his family estate. So did she. Living with a total stranger for twelve months is the only way Weston Thomas can claim possession of his Georgia family mansion. If not, the place goes to the dogs--seven rescue pups being looked after by Paige Martinson, his co-owner, to be exact. West's instant, unexpected attraction to the free-spirited ghostwriter comes with rules of engagement. But when chemistry deepens into more powerful emotions, is the accountant willing to bank on a future that was never in his long-term plans?"--